TREATMENT OF GENERALIZED PERIODONTITIS OF INITIAL STAGE IN PEOPLE WHO LIVES IN POLLUTED AREAS OF PRECARPATHIANS - I.Z. Chubij; M.M. Rozhko (Ukrainian Medical Stomatological Academy, 2015)
According to the research of a number of scientists in the application of laser therapy with antioxidant quercetin evident recovery system in periodontal tissues, improves blood and lymph circulation, trophic and metabolic processes, inhibites the growth of pathological granulation, reduces congestion and inflammation, shows normalization of cell membrane potential.  In our research we study 45 patients with generalized periodontitis that live in environmentally contaminated areas of Precarpathian. All patients were administered the complex treatment therapies that are commonly recommended for the treatment of patients with generalized periodontitis. In first group patients (22 individuals) were applied periodontal applications of quercetin as a gel for an individual silicone tooth-gingival sealed end. Patients of the second group (23 persons) were applied quercetin gel to the mucous membrane of the gums and it was activated by laser irradiation. For the purpose of comparative characteristics of two groups performed the index evaluation of periodontal tissues, cytomorphometric examination, radiographic, ultrasound examination of the born tissue. The results showed that the use of laser irradiation combined with quercetin in patients with generalized periodontitis stimulates metabolic processes in periodontal tissues, reduces cyanosis, edema in periodontal tissues. The results show that the usage of laser therapy in the treatment of patients with periodontitis of initial stages of development provides significant performance improvement of clinical treatment. The combination of quercetin gel that is activated by laser irradiation, shows significantly higher efficiency of the basic therapy for the treatment of clinical and laboratory examination methods.